Tuberculosis-Specific Antigen/Phytohemagglutinin Ratio Combined With GeneXpert MTB/RIF for Early Diagnosis of Spinal Tuberculosis: A Prospective Cohort Study - Qi, Yiwei; Liu, Zhiwei; Liu, Xiaojin; Fang, Zhong; Liu, Yanchao; Li, Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Spinal tuberculosis (TB), the most common form of musculoskeletal tuberculosis, is an infection-related disease globally, with paraplegia occurring in severe cases. Therefore, identification of spinal TB at an early stage is important for early intervention and eventual therapy. In this study, we conducted a prospective cohort study in routine clinical practice to investigate the diagnosis of different TB tests. A total of 519 patients were recruited based on the radiology of spinal TB. The diagnostic model was computed by regression analysis and was determined by receiver operating characteristic (ROC) curve analysis. Specificity, sensitivity, predictive value, likelihood ratio, and accuracy were also computed and compared. GeneXpert MTB/RIF showed a higher positive rate compared to that in the acid-fast bacilli smear and Mycobacterium culture. The results also showed that the Mycobacterium tuberculosis-specific antigen/phytohemagglutinin ratio in the T-SPOT assay had a good performance in the preoperative diagnosis and prediction of spinal TB. The diagnostic model based on the ratio of tuberculosis-specific antigen/phytohemagglutinin combined with GeneXpert MTB/RIF showed better efficiency for spinal TB diagnosis. In summary, the tuberculosis-specific antigen/phytohemagglutinin ratio combined with GeneXpert MTB/RIF could provide an early diagnosis of spinal TB.